2021
DOI: 10.12775/jehs.2021.11.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Similar neuroendocrine and metabolic effects of sulfate-chloride sodium-magnesium mineral waters "Myroslava" and "Khrystyna" of Truskavets’ spa in healthy female rats

Abstract: Background. In order to expand the hydro-mineral base of Truskavets’ spa by diluting brine (130 g/L), two new sulphate-chloride sodium-magnesium mineral waters "Myroslava" (5 g/L) and "Khrystyna" (10 g/L) were created. This report is the first in a series of experimental studies of their physiological activity in line with the concepts of neuroendocrine-immune complex and functional-metabolic continuum. Materials and Methods. Experiment was performed on 50 healthy female Wistar rats 220-300 g divided into 4 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In addition, it should be borne in mind that our patients used this water in combination with biologically active water Naftussya. However, the specificity of physiological effects was confirmed in an experiment on rats [1,9,10,11,24].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it should be borne in mind that our patients used this water in combination with biologically active water Naftussya. However, the specificity of physiological effects was confirmed in an experiment on rats [1,9,10,11,24].…”
Section: Discussionmentioning
confidence: 98%
“…The examination was performed twice, before and after a 7-10-day course of balneotherapy. Patients received bioactive water Naftussya (3 ml/kg one hour before meals three times a day) and in half an hour additionally drank sulfate-chloride sodium-magnesium water "Khrystyna" (5 g/L) or "Myroslava" (10 g/L) [11] in the same dose.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier in experiments on rats, it was shown that drinking mineral water, regardless of their mineralization and chemical composition, have similar (nonspecific) course effects on a number of parameters of metabolism and neuroendocrine-immune complex [1,10,11,23,36]. The aim of this study is to identify such parameters in patients of Truskavets resort who received complex drinking balneotherapy.…”
Section: Inroductionmentioning
confidence: 96%
“…"Myroslava" and "Khrystyna" mineral waters have both similar and different effects on the body of rats [1,11,12,24] and humans [8,13,14,25]. It is important that the differences are manifested not only in the severity of changes in the registered parameters, but also in their direction.…”
Section: Discussionmentioning
confidence: 99%